THE ROLE OF LEADERS IN EMPLOYEE RETENTION IN THE NON-FORMAL EDUCATION SECTOR - Nocita Maria; Romauli Nainggolan; Hastuti Naibaho (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of responsible leadership and transformational leadership on employee turnover intention in non-formal education institutions in Jakarta, with employee engagement serving as a mediating variable. This research employed a quantitative approach through a survey of 177 respondents selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that transformational leadership has a positive and significant effect on employee engagement (β = 0.504; p < 0.000), while responsible leadership does not significantly affect employee engagement (β = 0.005; p = 0.971). Employee engagement was found to be the strongest predictor in reducing turnover intention (β = -0.444; p < 0.000). Responsible leadership has a direct negative and significant effect on turnover intention (β = -0.355; p = 0.001), whereas transformational leadership does not have a significant direct effect on turnover intention (β = 0.188; p = 0.104). Employee engagement does not mediate the relationship between responsible leadership and turnover intention, but fully mediates the relationship between transformational leadership and turnover intention (β = -0.224; p < 0.001). The findings show that responsible leadership operates through ethical behavior and trust mechanisms that directly reduce turnover intention, while transformational leadership reduces turnover intention through the enhancement of employee engagement. This study extends Social Exchange Theory by demonstrating that different leadership styles operate through different mechanisms in influencing employee retention.